Patient-Reported Outcomes with Selpercatinib Treatment Among Patients with RET-Mutant Medullary Thyroid Cancer in the Phase I/II LIBRETTO-001 Trial. (30th September 2021) - Wirth, Lori J; Robinson, Bruce; Boni, Valentina; Tan, Daniel S W; McCoach, Caroline; Massarelli, Erminia; Hess, Lisa M; Jen, Min-Hua; Kherani, Jennifer; Olek, Elizabeth; Subbiah, Vivek
Abstract: Background: Medullary thyroid cancer (MTC) standard of care includes multikinase inhibitors (MKIs), which can exacerbate disease-related diarrhea, primarily because of non-RET kinase inhibition. We report diarrhea and other patient-reported outcomes (PROs) with selpercatinib, a highly selective RET inhibitor, among patients with RET -mutant MTC in the ongoing, phase I/II LIBRETTO-001 trial. Materials and Methods: Instrument completion time points were baseline (cycle 1, day 1) and approximately every other 28-day cycle until cycle 13 (every 12 weeks thereafter) for the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire-Core 30, and baseline, weekly during cycle 1, and day 1 of every cycle for the modified Systemic Therapy–Induced Diarrhea Assessment Tool (mSTIDAT). A ≥10-point change from baseline in domain score was considered clinically meaningful. PROs were summarized through cycle 13 in all patients and by subgroups with or without prior exposure to MKIs vandetanib and/or cabozantinib (V/C). Results: Among the overall MTC population ( n = 226), 88 (39%) and 124 (55%) patients comprised the V/C-naïve and previous V/C subgroups, respectively. Compliance was >85% for both instruments at each time point. Most patients maintained/improved in all health-related quality of life (HRQoL) subscales throughout treatment. Improvements in diarrhea were clinically meaningful in 43.5% of patients overall and in 36.8% and 51.3% of V/C-naïve and previous V/C subgroups, respectively. At baseline, 80.4% of all patients reported diarrhea on mSTIDAT. The percentage of patients who reported diarrhea was reduced to less than half of all patients (range: 33.3%–48.3%) after cycle 2. Conclusion: These interim results demonstrate that patients with RET -mutant MTC improved/remained stable on all domains of HRQoL during treatment with selpercatinib. Future analyses will be conducted as the data mature. Abstract : An objective of the LIBRETTO-001 trial was to describe patient-reported disease-related symptoms and health-related quality of life (HRQoL) during selpercatinib treatment, including time to improvement or worsening in patients with RET-mutant medullary thyroid cancer. In this interim analysis, patient-reported disease-related symptoms and HRQoL findings are summarized.